First record of Blattulidae from mid-Cretaceous Burmese amber (Insecta: Dictyoptera). (July 2019) - Qiu, Lu; Wang, Zong-Qing; Che, Yan-Li
Abstract: Blattulidae is an extinct cockroach family which was widely distributed around the world and lasted from Late Triassic to Cretaceous. Here we describe and illustrate the first blattulid genus found in the mid-Cretaceous Burmese amber, Huablattula gen. nov., to accommodate two new species, Huablattula hui sp. nov. and Huablattula jiewenae sp. nov. Most blattulid genera were only described based on inadequate samples, or were based only on nymphs, isolated tegmina, or wings. The well-preserved adult specimens described in this work not only fill a blank in Blattulidae study in Burmese amber, but also advance out knowledge of this family.